(untitled) (Scientific journal of the Fergana State University, 2024)
One of the direct methods of artistic psychologism - the letters included in the composition of the novel in philosophical-psychological novels not only move the plot, but also serve as a means of creating an artistic character, revealing the psyche and psychology of the hero.